2019
DOI: 10.1177/0300060519879287
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of one-time root canal treatment for irreversible pulpitis

Abstract: Objective To compare the therapeutic effects of one-time root canal treatment versus two-time treatment in patients with irreversible pulpitis. Methods We classified 130 patients into a one-time treatment group (group A; n = 68) and a two-time treatment group (group B; n = 62) according to the number of patient visits. Clinical efficacy at 6 months and 1 year follow-ups as well as serum levels of interleukin-6, tumor necrosis factor alpha, and high-sensitivity C-reactive protein before and 1 week after endodon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
0
14
0
3
Order By: Relevance
“…Root canal therapy is a key treatment for pulpitis. It can effectively remove adverse irritation, clean up the source of infection in the root canal, prevent the spread of infection, and improve clinical symptoms by removing necrotic or gangrene substances in the root canal [ 11 ]. This technique is easy to operate.…”
Section: Discussionmentioning
confidence: 99%
“…Root canal therapy is a key treatment for pulpitis. It can effectively remove adverse irritation, clean up the source of infection in the root canal, prevent the spread of infection, and improve clinical symptoms by removing necrotic or gangrene substances in the root canal [ 11 ]. This technique is easy to operate.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed higher levels of proinflammatory cytokines tumour necrosis factor, interleukin (IL)-6, and IL-1B during and after root canal treatments. 20 , 21 , 22 The same cytokines have similarly been associated with dystrophic calcification. 23 The mutual presence of proinflammatory cytokines in both situations support the assumption that intra-oral inflammatory events, which result from dental pathologies and advanced dental treatments, are associated with SHL calcifications.…”
Section: Discussionmentioning
confidence: 89%
“…At present, the main clinical treatment of pulpitis is root canal treatment, which can achieve good results 13 . The root canal treatment of pulpitis requires the thorough removal of residual tissue and debris in the root canal system, as well as the effective elimination of bacteria and their complex product 13 .…”
Section: Discussionmentioning
confidence: 99%